2023
DOI: 10.3389/fpls.2022.1085915
|View full text |Cite
|
Sign up to set email alerts
|

A non-targeted metabolomics analysis identifies wound-induced oxylipins in Physcomitrium patens

Abstract: Plant oxylipins are a class of lipid-derived signaling molecules being involved in the regulation of various biotic and abiotic stress responses. A major class of oxylipins are the circular derivatives to which 12-oxo-phytodienoic acid (OPDA) and its metabolite jasmonic acid (JA) belong. While OPDA and its shorter chain homologue dinor-OPDA (dnOPDA) seem to be ubiquitously found in land plants ranging from bryophytes to angiosperms, the occurrence of JA and its derivatives is still under discussion. The bryoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Our results suggest that OPDA and dn‐OPDA biosynthesis emerged in charophytes and is conserved in land plants. These results are consistent with previous detection of these two molecules in K. nitens , M. polymorpha , P. patens, H. selago and A. thaliana (Koeduka et al ., 2015; Chini et al ., 2018; Monte et al ., 2018, 2020, 2022; Mukhtarova et al ., 2020; Resemann et al ., 2023). Consistently, we found putative orthologous AOS sequences in all analysed streptophytes lineages but not in chlorophytes, whereas AOC orthologs were exclusively present in land plants (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that OPDA and dn‐OPDA biosynthesis emerged in charophytes and is conserved in land plants. These results are consistent with previous detection of these two molecules in K. nitens , M. polymorpha , P. patens, H. selago and A. thaliana (Koeduka et al ., 2015; Chini et al ., 2018; Monte et al ., 2018, 2020, 2022; Mukhtarova et al ., 2020; Resemann et al ., 2023). Consistently, we found putative orthologous AOS sequences in all analysed streptophytes lineages but not in chlorophytes, whereas AOC orthologs were exclusively present in land plants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to A. thaliana , the JA‐Ile precursors OPDA and dn‐ cis ‐OPDA have been described in different nonvascular species including the bryophytes P. patens and M. polymorpha and the charophyte alga K. nitens , suggesting that the origin of OPDA/dn‐OPDA biosynthesis predates land plant colonization (Weber et al ., 1997; Stumpe et al ., 2010; Koeduka et al ., 2015; Chini et al ., 2018; Monte et al ., 2018, 2020). Conversely, the presence of JA/JA‐Ile in algae, bryophytes and lycophytes is controversial (Scholz et al ., 2012; Beilby et al ., 2015; Koeduka et al ., 2015; Záveská Drábková et al ., 2015; Monte et al ., 2018; Nishiyama et al ., 2018; Široká et al ., 2022; Resemann et al ., 2023) and it has been proposed that JA‐Ile biosynthesis emerged in lycophytes (Pratiwi et al ., 2017). To clarify the evolution of the JA‐Ile biosynthetic pathway and the distribution of bioactive jasmonates in the green lineage, we performed phylogenetic analyses and jasmonate profiling in representative species covering the main clades of green algae and land plants under control or stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to A. thaliana , the JA-Ile precursors OPDA and dn- cis -OPDA have been described in different non-vascular species including the bryophytes Physcomitrium patens (formerly Physcomitrella patens) and M. polymorpha and the charophyte alga K. nitens , suggesting that the origin of OPDA/dn-OPDA biosynthesis predates land plant colonization (Weber et al, 1997; Stumpe et al, 2010; Koeduka et al, 2015; Chini et al, 2018; Monte et al, 2018, 2020). Conversely, the presence of JA/JA-Ile in algae, bryophytes and lycophytes is controversial (Scholz et al, 2012; Beilby et al, 2015; Koeduka et al, 2015; Záveská Drábková et al, 2015; Monte et al, 2018; Nishiyama et al, 2018; Široká et al ., 2022; Resemann et al ., 2023) and it has been proposed that JA-Ile biosynthesis emerged in lycophytes (Pratiwi et al, 2017). To clarify the evolution of the JA-Ile biosynthetic pathway and the distribution of bioactive jasmonates in the green lineage, we performed phylogenetic analyses and oxylipin metabolomic profiling in representative species covering the main clades of green algae and land plants under control or stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Because liverworts, mosses, and green algae contain AOS enzymes [29,30,32], it is suggested that the introduction of AOS genes occurred before the evolution of terrestrial plants, and AOS enzymes were likely present in the last common ancestor of plants and animals [14,34]. Recently, a metabolic analysis of wounded Physcomitrium patens Mitt knockout mutants of the PpAOS1 gene uncovered that this enzyme is responsible for the synthesis of two α-ketols [39]. Available data suggest that dual-specific AOS enzymes localized either to cytosol or chloroplast likely evolved before the evolution of flowering plant species [14,29,34].…”
Section: Biosynthesis and Occurrence Of Ketolsmentioning
confidence: 99%